OPTIMISATION STUDIES ON RUBBER SEED OIL BASED METHYL ESTER SYNTHESIS VIA HYDRODYNAMIC CAVITATION TECHNOLOGY - SHAH BOKHARI, SYED AWAIS ALI (2018)
Hydrodynamic cavitation (HC) technology is a viable way to produce sustainable biodiesel from high free fatty acid non-edible feedstock. This technology has affirmative environmental impacts with lower energy consumption and shorter reaction time, which offers a cleaner possibility. The limitation of conventional mechanical stirring (MS) process involved longer reaction time to obtain methyl ester content. Four newly designed orifice plates were studied as a cavitating device in HC reactor. HC reactor was connected to the diaphragm pump in a close loop reactor. The compressed air was supplied to operate the double diaphragm pump, which is the main device to dissipate the energy in a HC reactor